Anti-thrombocytopenic activity of ipomoea batatas (L.) Lam (Sweet potato) green aqueous leaf extract in anagrelide-induced thrombocytopenia in rattus norvegicus (Sprague-Dawley Rats) - Arago, Zyron Ken P. Camacho, Jose Martin L. Lachica, Regina Beatrice D. Macaraeg, Gerry Mari S. Ong, Marxienne Leinnix Mazette D. 4 0 16; 5
ABSTRACT: Thrombocytopenic conditions arise when the platelet count falls below the normal range's lower limit (150000/microliter). complications ranging from simple petechiae and bood spots io gastrointestinal bleeding. hemorrhage, and severe cerebrospinal fluid bleeding. Current drugs used to treat this condition have substantial negative effects. This research aims to establish the most effective concentration of extract that will result in a significant percentage platelet increase within 7 days. 24 female Sprague-Dawley rats aged 6-8 weeks were randomly divided into 4 groups of 6. The platelet baseline count was established by injecting 0.08 mg/Kg BW anagrelide through the tail vein for 3 days. Intravenous (IV) bolus injections of 5 mL/Kg BW dosage volume with Ipomea batatas leaf extract concentrations of 100 mg/Kg, 300 mg/Kg, and 500 mg/Kg were administered to Groups A, B, and C, respectively for 7 days. The untreated group was given 1 mL of distilled water orally. The results showed that all three concentrations of Ipomea batatas that were tested increased in the platelet levels of the test animals, with the 500 mg/Kg concentration showing the highest increase among the three concentrations. Keywords: thrombocytopenia, Ipomoea batatas, platelet augmentation
Undergraduate Thesis: (Bachelor of Science in Biology) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2